Up-date on Joint Forest Management Programme in Andhra Pradesh - Mukherji, S. D. (Indian Forester, 1998)
The Joint Forest Management Programme is being implemented with full vigour and with the active involvement ofViUage level Vana Samarakshana Sarnithies (VSS) in Andhra Pradesh. It has now corne to a stage where positive results can be seen. Some of the VSS formed in 1993 are to-day in a position to harvest the first rotation crop after successfully protecting the forests and improving it. This programme will be sustained and the degraded forests of Andhra Pradesh would be regenerated giving maximum benefit to the local people.